ANALYSIS OF THE EFFECT OF ESG DISCLOSURE ON FINANCIAL PERFORMANCE AND FIRM VALUE IN ENERGY SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Rosidawaty; Andika Mugi Gumilang; Tanti Septiani; Ingkak Chintya Wangsih (RADJA PUBLIKA, 2026)
This study examines the influence of Environmental, Social, and Governance (ESG) disclosure on firm performance within the energy sector listed on the Indonesia Stock Exchange (IDX) over the period 2020–2024. The primary objective is to evaluate the effect of ESG disclosure, measured using indicators based on the Global Reporting Initiative (GRI) Standards, on three key financial performance metrics: Return on Assets (ROA), Return on Equity (ROE), and Tobin’s Q. Adopting a quantitative approach with a causal-associative research design, the study utilizes secondary data derived from annual and sustainability reports of 18 energy companies that consistently disclosed ESG information over five consecutive years, resulting in 90 firm-year observations. Data were analyzed using multiple linear regression with the support of SPSS version 25. The findings indicate that ESG disclosure has a statistically significant positive effect on ROE, whereas its impact on ROA and Tobin’s Q is not significant. These results imply that ESG disclosure may enhance shareholder returns but does not substantially influence operational efficiency or market valuation. The study suggests that companies should improve the quality and substance of ESG disclosures, and recommends that future research incorporate moderating or mediating variables to better capture the dynamics between ESG practices and firm performance.